Implementasi Program Pelatihan Menjahit Pakaian Wanita Bagi Peserta Didik Untuk Meningkatkan Kecakapan Hidup Di BPVP Kota Samarinda - Ridwan Ridwan; Zaenab Hanim; Misnawati Misnawati; Murni Murni (Journal on Education, 2023)
Training is a part of education which contains a short duration learning process and is organized in a systematic and structured manner. This training aims to identify training on the implementation of sewing women's clothing for students to improve life skills at BPVP Samarinda City. Research subjects obtained from the results of data collection in the form of interviews, observation and documentation. The subjects of the interview data in the form of resource persons from this study consisted of the heads of the women's clothing sewing department programs, training instructors and training participants in women's clothing sewing. This study uses a descriptive research method with a qualitative approach. The data collection techniques in this study used interview, observation and documentation techniques. While the data analysis techniques in this study used data collection, data reduction, data presentation and drawing conclusions. The results of this study include: The stages of training needs analysis using observation and field surveys according to what is needed as well as planning and preparing instructors as the basis for forming a training, so that training planning is a procedure to achieve a predetermined goal, and using the implementation training method is a process of implementing training, with the implementation of training methods can run optimally, and the next stage is training evaluation one of the tools used in assisting program planning and improving the training program, self-evaluation can be used as a level of effectiveness of a program. - Factors that influence the success of the training process selling women's clothing, namely the existence of instructors, training participants and facilities and infrastructure.